The conception of EU-Russia strategic partnership: Reasons of its failure - Pablo Podadera Rivera; Anna Garashchuk (Atlantic Review of Economics, 2016)
The present paper seeks the aim to analyse the Euro-Russian relationship in the context of current situation of the political crisis provoked by the incident in Ukraine and to compare it with the elaborated model of the “Strategic Partnership”. This analysis should help us to investigate why the conception of the strategic partnership between the European Union and the Russian Federation has failed and if the revision of the relationship and turning into real strategic partners still has a sense?
Keywords: 330; Euro-Russian relationship; political crisis; conflict in Ukraine; Strategic Partnership between the EU and the RF; strategic partners; interdependence